Network and application security assessment / Norizam Idris - Idris, Norizam (2004)
Assessment of network and application security is the process of detecting, recording and auditing to come out with a schema network security measurement. Prevention measures help you to stop unauthorized users (also known as"intruders") from accessing any part of your computer system. Detection helps you to determine whether or not someone attempted to break into your system, if they were successful, and what they may have done. This section provides a basic introduction to the technologies that underlie the network technology. It was written with the novice end-user in mind and is not intended to be a comprehensive survey of all network -based technologies The security assessment that was conducted focus on four distinct areas that were assessed separately. These areas were Application security, Host security, Network Security and Disaster Recovery